The Effect of Capital Structure, Liquidity, and Asset Efficiency on Company Value - Rina Sumarni; Fanlia Prima Jaya; Diana; Rezti; Arfie Yasrie (Economic and Business Horizon, 2026)
Increasing economic uncertainty, fluctuations in interest rates, and evolving business dynamics have compelled companies to optimize their financial policies to enhance company value. This study aims to examine the effects of capital structure, liquidity, and asset efficiency on company value. Employing a quantitative approach with a causal-associative research design, this study utilizes secondary data obtained from the company’s annual financial statements covering the period of 2015–2024. The variables examined include capital structure, liquidity, and asset efficiency as independent variables, while company value serves as the dependent variable. Data were analyzed using multiple linear regression with the assistance of SPSS version 25, following a series of classical assumption tests. The findings indicate that capital structure has a significant negative effect on company value, whereas liquidity and asset efficiency have significant positive effects on company value. Furthermore, the three independent variables simultaneously exert a significant influence on company value and collectively explain a substantial proportion of its variation. These results suggest that maintaining an optimal financing structure, preserving adequate liquidity, and improving asset utilization efficiency are essential for enhancing long-term company value and competitiveness.